Promotion of agribusiness in northern Finland by development of production and cultivation technologies for special plants - Virtanen, Vesa; Kajalo, Markku; Korhonen, Jari; Moilanen, Tarja (SIOKIS Medical & Scientific Publishers, 2005)
v ok